2021
DOI: 10.1021/acs.inorgchem.0c02742
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Derived Non-Heme Iron and Manganese Complexes: Catalysts for the On-Demand Production of Chlorine Dioxide in Water under Mild Conditions

Abstract: A lignin-derived ligand, bis(2-hydroxy-3-methoxy-5propylbenzyl)glycine (DHEG), was synthesized from 2-methoxy-4propylphenol (dihydroeugenol (DHE)) and the amino acid glycine. Two mononuclear iron and manganese complexes of DHEG were prepared, characterized, and employed for the oxidation of chlorite to chlorine dioxide in aqueous solution. Peroxyacetic acid (PAA) was used as a "green" oxidant in the redox reactions to initiate the formation of high-valent Fe and Mn (IV)−OH intermediates. EPR studies verified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…ClO 2 has a boiling point of 11 • C, a melting point of −59 • C, a density of 1.64 g mL −1 (liquid) at 0 • C [25], a water solubility of 3.0 g L −1 at 25 • C [17], and pKa value of 3.0. ClO 2 is strongly soluble in water and does not hydrolyze to any appreciable extent but remains in solution as a dissolved gas [26]. ClO 2 in aqueous solutions is quite stable when protected from light and kept cool, well-sealed, and slightly acidified (pH = 6).…”
Section: Clo 2 Physicochemical Propertiesmentioning
confidence: 99%
“…ClO 2 has a boiling point of 11 • C, a melting point of −59 • C, a density of 1.64 g mL −1 (liquid) at 0 • C [25], a water solubility of 3.0 g L −1 at 25 • C [17], and pKa value of 3.0. ClO 2 is strongly soluble in water and does not hydrolyze to any appreciable extent but remains in solution as a dissolved gas [26]. ClO 2 in aqueous solutions is quite stable when protected from light and kept cool, well-sealed, and slightly acidified (pH = 6).…”
Section: Clo 2 Physicochemical Propertiesmentioning
confidence: 99%
“…The latest research has confirmed the critical contribution of high-valent metal species to organic contaminant oxidation owing to their long half-lives and high selectivity toward organics. , Thus, high-valent metal species and ClO 2 during chlorite activation enable selective oxidation of organics, which would further eliminate the aquatic biotoxicity. Despite the successful production of ClO 2 in metalloporphyrin-catalyzed chlorite activation, ,, the potential of high-valent metal species and ClO 2 generated in chlorite activation for the selective oxidation of contaminant was greatly neglected. The development of a novel oxidation technique based on chlorite activation will pave a way for selective oxidation of organics in contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Practical applications and exotic kinetic phenomena have generated considerable interest in the chemistry of chlorite ion that has been utilized as oxidizing agent in very diverse areas. Chlorite ion is also the precursor in the generation of chlorine dioxide, which has extensively been used in water and wastewater treatment technologies, cellulose bleaching, disinfection processes, deactivation of Bacillus anthracis spores, food industry, etc. , In these systems, chlorine(I) always forms as an intermediate and, in turn, is involved in complex reactions with chlorite ion yielding Cl – , ClO 2 , and ClO 3 – in variable concentration ratios depending on the actual conditions. According to earlier studies, the stoichiometry of this reaction is very sensitive to the pH, the concentrations as well as the concentration ratios of the reactants, and the presence of additional components that may act as promoters or inhibitors in the overall process. In general, the stoichiometry can be defined as the linear combination of eqs and . ClO 2 + HOCl = ClO 3 + Cl + normalH + 2 ClO 2 + HOCl + normalH +…”
Section: Introductionmentioning
confidence: 99%